2014
DOI: 10.1002/pbc.25241
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of kaposiform hemangioendothelioma with everolimus

Abstract: There is currently no consensus on the second-line management of Kaposiform hemangioendothelioma (KHE) that was resistant to prednisolone and vincristine. We described an eight-year-old male with KHE in the right femur that was resistant to prednisolone, vincristine and propranolol. Everolimus, an inhibitor of mammalian target of rapamycin (mTOR) at the dosage of 0.1 mg/kg/day, successfully decreased the tumor size and controlled the symptoms. Everolimus should be further studied as an alternative agent to sir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 11 publications
1
32
0
2
Order By: Relevance
“…This recommendation was largely based on evidence using sirolimus [54], but several case reports have described successful outcomes for Kaposi's sarcoma in kidney transplant patients following conversion to everolimus [48, 52, 55, 56] (Table 1). These cases, while limited, are consistent with the available evidence relating to management of Kaposi's sarcoma in nontransplanted individuals by everolimus alone [5860]. …”
Section: Kidney Transplantationsupporting
confidence: 80%
“…This recommendation was largely based on evidence using sirolimus [54], but several case reports have described successful outcomes for Kaposi's sarcoma in kidney transplant patients following conversion to everolimus [48, 52, 55, 56] (Table 1). These cases, while limited, are consistent with the available evidence relating to management of Kaposi's sarcoma in nontransplanted individuals by everolimus alone [5860]. …”
Section: Kidney Transplantationsupporting
confidence: 80%
“…Li Kai et al reported another six cases with KHE and KMP and refractory to at least two medical therapies, which responded to sirolimus with shrinkage of the tumor mass and resolution of KMP [14]. Uno et al applied another mTOR inhibitor, everolimus, in a patient with KHE and KMP with satisfactory result and minimal side effects, following unsuccessful therapy with propranolol, prednisolone, and cytostatics [26].…”
Section: Discussionmentioning
confidence: 97%
“…This patient had significant response to sirolimus treatment and rapid improvement in platelet count and fibrinogen level after failure of all standard treatment algorithms 14 . In the last few years, multiple studies, including case reports and retrospective case series, have been reported using sirolimus for treatment of different vascular anomalies with positive results 4, 12, 15, 16, 17, 18, 19, 20, 21, 22. A 2011 study on 6 patients found that sirolimus is a reasonable treatment for children and young adults with complicated vascular anomalies, even when they have proven refractory to several other treatments 23 .…”
Section: Discussionmentioning
confidence: 96%
“…Sirolimus is a macrocyclic triene antibiotic produced by Streptomyces hygroscopicus, a streptomycete isolated from a soil sample collected from Easter Island (Rapa Nui). Although sirolimus is a potent antifungal agent, several studies found that sirolimus is a serine/threonine kinase regulated by phosphoinositide 3-kinase and acts as a master switch of numerous cellular processes, including cell growth and angiogenesis; it has a potent antitumor and immunosuppressive activity 12, 13…”
Section: Discussionmentioning
confidence: 99%